Kebijakan Kriminal Pencegahan Korupsi Pelayanan Publik - Satria, Hariman Satria (Komisi Pemberantasan Korupsi, 2020)
The widespread of corruption in public services is not only triggered by its poor system but also by the moral vulnerability of the state officials. This study aims to give a comprehensive account of the prevention of corruption in public services, specifically in the criminal policy domain. The study presents normative legal research through statute and conceptual approaches. In line with the corruption issue, the government needs to take adequate and relevant strategies to eradicate corruption. They include adopting crime prevention theory such as situational crime prevention, enhancing ethical and professional employee culture through good corporate governance, imposing strict sanctions for unprofessional employees, maximizing incentives for professional employees, disseminating massive and systematic impact of corruption in natural resource sectors, implementing an integrated online-based licensing system, reforming the public service, and improving the license approval process.